2014
DOI: 10.2118/159747-pa
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of Buoyancy-Assisted Tubulars

Abstract: Use of buoyancy provides multiple solutions to overcome the drag problem for wells with shallow and high step-out profiles. Although both full-and partial-flotation methodologies have been used successfully to extend the reach in many field cases, the influence of buoyancy on tubular instability has not been investigated yet. This paper presents an extensive experimental and analytical study, focusing on static tubular instability inside horizontal wellbores with emphasis on buoyancy. In terms of the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The effective force Feff is usually derived in calculations from the magnitude of the true force by taking into account the stability force Fbs according to expressions (6,8). Studies of the drill string stresses in the fluid have shown [8,9] that accounting for the stability force Fbs leads to the exclusion of the hydrostatic component from the stresses in the drill string, which does not affect the buckling of the drill string, as well as the strength of the plastic materials from which the drill string elements are usually made. Therefore, effective force is widely used to check buckling conditions, which is one of the most important requirements for the operability of the drill string.…”
Section: Discussionmentioning
confidence: 99%
“…The effective force Feff is usually derived in calculations from the magnitude of the true force by taking into account the stability force Fbs according to expressions (6,8). Studies of the drill string stresses in the fluid have shown [8,9] that accounting for the stability force Fbs leads to the exclusion of the hydrostatic component from the stresses in the drill string, which does not affect the buckling of the drill string, as well as the strength of the plastic materials from which the drill string elements are usually made. Therefore, effective force is widely used to check buckling conditions, which is one of the most important requirements for the operability of the drill string.…”
Section: Discussionmentioning
confidence: 99%
“…Directing at the theoretical models above, Arslan [21] measured the buckling critical load of a horizontal string through an experiment with the experimental setup as shown in Fig. 2.…”
Section: Model Verificationmentioning
confidence: 99%
“…The parameters used in numerical simulation are as literature [21]. The length of the pipe is 28 m. Outer and inner diameters of the inner pipe are 19 and 17 mm, respectively.…”
Section: Model Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have focused in comparing results obtained from literature models with experimentally measured data, such as in Arslan et al (2014); or improving even further the models for the static configuration after buckling, as in Huang et al…”
Section: Column Bucklingstatic Approachmentioning
confidence: 99%